Shear Initiation from Low Velocity Impact - Partom, Y. (European Journal of Applied Sciences, 2023)
Ignition and initiation by low velocity impact are usually investigated experimentally by the so-called Steven test. In this test a heavy steel projectile is launched against a steel sandwich target containing the tested explosive. The output is monitored by blast gauges three meters from the target. The test results are in terms of the threshold impact velocity for ignition, and of the TNT equivalent of the tested explosive as a function of impact velocity beyond this threshold. To date there is no accepted model that can predict the outcome of a Steven test or any other low velocity impact event. There is a great demand for such a model for explosive safety issues. In this paper we propose a model to predict the outcome of a low velocity impact event. The model is simple to use in a hydrocode, and goes over smoothly to shock initiation and detonation phases of the impact event. We calibrate the model from Steven test data, and we then use it to predict the propagation of the deflagration wave in a Steven test.